Solve for x > 0 ,
( 1 2 x − 1 ) ( 6 x − 1 ) ( 4 x − 1 ) ( 3 x − 1 ) = 5
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great manipulation.
I Have Very short method for This Question.
let
1 2 x − 1 = t .
so eqn becomes:
t ( t − 1 ) ( t − 2 ) ( t − 3 ) = 5 ∗ 4 ∗ 3 ∗ 2 .
t = 5 .
x = 1 / 2 = 0 . 5 .
Q.E.D
Best Solution..!!
awesome and fantastic!!
( 1 2 x − 1 ) ( 6 x − 1 ) ( 4 x − 1 ) ( 3 x − 1 ) = 5
L A T E X
Multiply both sides by 1 ⋅ 2 ⋅ 3 ⋅ 4
1 ⋅ ( 1 2 x − 1 ) ⋅ 2 ⋅ ( 6 x − 1 ) ⋅ 3 ⋅ ( 4 x − 1 ) ⋅ 4 ⋅ ( 3 x − 1 ) = 5 ⋅ 4 ⋅ 3 ⋅ 2 ⋅ 1
( 1 2 x − 1 ) ( 1 2 x − 2 ) ( 1 2 x − 3 ) ( 1 2 x − 4 ) = 5 ⋅ 4 ⋅ 3 ⋅ 2 ⋅ 1
L A T E X
Let a = 1 2 x − 1
( 1 2 x − 1 ) ( 1 2 x − 1 − 1 ) ( 1 2 x − 1 − 2 ) ( 1 2 x − 1 − 3 ) = 5 ⋅ 4 ⋅ 3 ⋅ 2 ⋅ 1
L A T E X
Definition of a factorial:
a ( a − 1 ) ( a − 2 ) ( a − 3 ) = 5 ⋅ 4 ⋅ 3 ⋅ 2 ⋅ 1
a ! = 5 !
a = 5
5 = 1 2 x − 1
x = 2 1
The factorial step is invalid since − 2 satisfies the equation, and it is not known whether a can be a nonnegative integer or not.
Log in to reply
If a = − 2 , will it satisfy the representation for a = 1 2 x − 1 ?
Note that it is known that x > 0 . From there, we shall know the range of values of a: ( − 1 , ∞ )
Clearly, -2 is out of range.
Although I think what you meant was that factorial step isn’t necessary.
And in that case, I happen to observe that it follows a pattern and that I immediately associated it to factorials.
Problem Loading...
Note Loading...
Set Loading...
( 1 2 x − 1 ) ( 6 x − 1 ) ( 4 x − 1 ) ( 3 x − 1 ) = 5
∴ ( ( 1 2 x − 1 ) ( 3 x − 1 ) ) ( ( 6 x − 1 ) ( 4 x − 1 ) ) = 5
∴ ( 3 6 x 2 − 1 5 x + 1 ) ( 2 4 x 2 − 1 0 x + 1 ) = 5
∴ ( 3 ( 1 2 x 2 − 5 x ) + 1 ) ( 2 ( 1 2 x 2 − 5 x ) + 1 ) = 5
Let 1 2 x 2 − 5 x = t
∴ ( 3 t + 1 ) ( 2 t + 1 ) = 5
∴ 6 t 2 + 5 t − 4 = 0
Solving the quadratic we obtain the roots as:
t = 2 1 or t = 3 − 4
Case 1:
1 2 x 2 − 5 x = 2 1
∴ 2 4 x 2 − 1 0 x + 1 = 0
∴ x = 2 1 or x = 1 2 − 1
Since only positive solutions are required we shall discard x = 1 2 − 1
Case 2:
1 2 x 2 − 5 x = 3 − 4
∴ 3 6 x 2 − 1 5 x + 4 = 0
As this equation yields complex roots we shall discard them.
Thus the required answer is x = 0 . 5